In situ soil COS exchange of a temperate mountain grassland under simulated drought - Kitz, Florian (Oecologia, 2017)
During recent years, carbonyl sulfide (COS), a trace gas with a similar diffusion pathway into leaves as carbon dioxide (CO(2)), but with no known “respiration-like” leaf source, has been discussed as a promising new approach for partitioning net ecosystem-scale CO(2) fluxes into photosynthesis and respiration. The utility of COS for flux partitioning at the ecosystem scale critically depends on the understanding of non-leaf sources and sinks of COS. This study assessed the contribution of the soil to ecosystem-scale COS fluxes under simulated drought conditions at temperate grassland in the Central Alps. We used transparent steady-state flow-through chambers connected to a quantum cascade laser spectrometer to measure the COS and CO(2) gas exchange between the soil surface and the atmosphere. Soils were a source of COS during the day, emissions being mainly driven by incoming solar radiation and to a lesser degree soil temperature. Soil water content had a negligible influence on soil COS exchange and thus the drought and control treatment were statistically not significantly different. Overall, daytime fluxes were large (12.5 ± 13.8 pmol m(−2) s(−1)) in their magnitude and consistently positive compared to the previous studies, which predominantly used dark chambers. Nighttime measurements revealed soil COS fluxes around zero, as did measurements with darkened soil chambers during daytime reinforcing the importance of incoming solar radiation. Our results suggest that abiotic drivers play a key role in controlling in situ soil COS fluxes of the investigated grassland. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00442-016-3805-0) contains supplementary material, which is available to authorized users.